MER4 endogenous retrovirus correlated with better efficacy of anti-PD1/PD-L1 therapy in non-small cell lung cancer - Francois Ghiringhelli; Romain Boidot; Caroline Truntzer; Bertrand Routy; Philippe Joubert; Julie Lecuelle; Laure Favier; Cléa Fraisse; Aurélie Lagrange; Coureche Kaderbhai; Sandy Chevrier (Journal for ImmunoTherapy of Cancer)
Background Endogenous retroviruses (ERVs) are highly expressed in various cancer types and are associated with increased innate immune response and better efficacy of antiprogrammed death-1/ligand-1 (anti-PD1/PD-L1)-directed immune checkpoint inhibitors (ICI) in preclinical models. However, their role in human non-small cell lung cancer (NSCLC) remains unknown.Methods We conducted a retrospective study of patients receiving ICI for advanced NSCLC in two independent cohorts. ERV expression was determined by RNA sequencing. The primary endpoint was progression-free survival (PFS) under ICI. The secondary endpoint was overall survival (OS) from ICI initiation. We studied expression of 6205 ERVs. Multivariate Cox regression model with lasso penalty was estimated on the training set to select ERVs significantly associated with survival. The predictive power of these ERVs was compared with that of previously described transcriptomic signatures.Results We studied two independent cohorts of 89 and 70 patients, used as training and validation sets. Clinicopathological characteristics included 75% of patients with non-squamous NSCLC. We selected four ERVs significantly associated with PFS. Only high MER4 ERV was associated with better PFS and OS in both cohorts. From a biological point of view, high MER4 expression is associated with higher infiltration of eosinophils and inflammatory gene signatures, while low MER4 expression is associated with enrichment in metabolism and proliferation signatures. Adding MER4 to previously described transcriptomic signatures of response to ICI improved their predictive power.Conclusions MER4 ERV expression is useful to stratify risk and predict PFS and OS in patients treated with ICI for NSCLC. It also improves the predictive power of other known transcriptomic signatures.